Influence of Titania Dispersivity on the Conversion Efficiency of Dye-Sensitized Solar Cells - Yasuhiro Yamamoto; Yukihiro Aoyama; Sumiyo Shimizu; Junya Kano; Fumio Saito; Seigo Ito (International Journal of Photoenergy)
Titania powder (P25) was dispersed by bead-milling breakdown method, and the dispersivity of TiO2 was controlled by adjusting the mean secondary TiO2 particle size to 45, 56, and 75 nm by changing the dispersion solvent blend ratio of ethanol and terpineol. The transparency of the coated layer increased when the particle size of TiO2 aggregates became smaller than 100 nm. Although the transparency was significantly different according to differences in the size of nanocrystallyne-TiO2 aggregates, the resulting photovoltaic (PV) effect of a dye-sensitized solar cell (DSSC) was not significantly different between the different aggregate sizes. A double layer structure (transparent TiO2 layer/opaque TiO2 layer) was adopted to improve the PV effect, which resulted in an improvement of the photocurrent and conversion efficiency of 13.2% and 11.1%, respectively, from that for the DSSCs with single-layered TiO2 electrodes.